Perbandingan Efektivitas Dalam Pengelolaan Lembaga Pemasyarakatan (Lapas) Yang Mengalami Overcrowded di Negara Indonesia dan Brasil - Rizki Pratama, Muh Ersandi; Ansa, Ferdi; Irfandi, Fitra; Hafiidz Syam, Syahrul (LPPM Universitas Ekasakti Padang, 2024)
Indonesia is a country based on law. In addition to using the term rechtstaat, Indonesian literature also commonly uses another term, namely the rule of law, to mean